SM-ND ISOTOPIC SYSTEMATICS OF METABASITES FROM THE ARCHEAN SUTAM COMPLEX OF GRANULITES (SOUTHERN ALDAN SHIELD) - Mishkin M.A.; Lavrik S.N.; Vovna G.M.; Oktyabr'skii R.A.; Karpenko S.F. (My University, 2000)
The paper presents first data on the Sm-Nd isotopic systematics of metabasites from the supracrustal Sutam granulite complex (South Aldan Shield). It is established that the formation time of protoliths of mafic and ultramafic crystalline schists, which are conformable to the host enderbites, is 3067 ± 130 Ma. This date is close to the known U-Pb age of 3131 ± 74 Ma characterizing protolith of enderbite plagiogneisses of the Sutam complex. The result obtained suggests that the commencement of the early sialic crust formation in the southern Aldan Shield was not in the Early Archean, as had been customary accepted before, but near the Early-Late Archean boundary. The event was marked by an intense andesite-dacite volcanism and associated eruptions of basic and ultrabasic magmas.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей